Potensi Limbah Kulit Biji Kopi dan Pemanfaatannya sebagai Produk Sabun Cair yang memiliki Aktivitas Antioksidan dan Antibakteri: Potential of Coffee Bean Peel Residue and Its Use in a Liquid Soap with Antioxidant and Antibacterial - Fith Khaira Nursal; Anisa Amalia; Supandi Supandi; Nining Nining; Yeni Yeni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Numerous coffee plantation workers are members of the Neglasari village farmer group, located in Sukawangi village, Bogor district. The problem frequently raised is coffee bean residue, which is typically discarded and provides an idea for the group to consider using it. This issue can be remedied by providing knowledge and direction regarding possible coffee bean husk residues. According to earlier studies, coffee bean skin includes polyphenols with potential antibacterial and antioxidant properties, allowing it to be formulated into skin-safe liquid soap solutions. Participants are productive-age men and female farmers with a constant motivation for entrepreneurship. Participants were provided with a direct explanation of the possibilities of coffee bean husk residue, followed by a short training on manufacturing liquid soap. Comparing the outcomes of the pre-test and post-test provided to participants is an indication of the activity's efficacy. Based on the collected results, it can conclude that the participant's comprehension of the presented material increased significantly (p < 0.05). It anticipated that the outcomes of this product development education and training would enable Farmer Group members to become home-based entrepreneurs.